Effects of Home Tutoring Programme on Reading Achievement of Primary School Children with Dyslexic Learning Disabilities in Chanchaga Local Government Area, Niger State, Nigeria - Liman, Nalado A.; Ihenacho, Zika John (NIU Journal of Humanities; Vol 4 No 3 (2019): KIU Journal of Humanities, Vol. 4 No. 3, September 2019, 2019)
This study looked at the effects of home tutoring programme on reading achievement of primary school children with dyslexic learning disability in Chanchaga Local Government Area of Niger state, Nigeria. The study adopted quasi experimental design, and particularly it employed the pretest - posttest control – experimental group design. A sample of eight (8) pupils was taken (four in the experimental and four in the control group). Three research questions and three hypotheses guided the study. The instrument for data collection was the Reading Achievement Inventory (RAI), which was validated and found to be appropriate for the study. Data analyses were done using simple percentage, mean difference and gain scores to answer research questions and t-Test to answer the hypotheses. The results obtained revealed that children taught using home tutoring programme performed better than children taught with the conventional method on all the variables under study, and it was recommend that parents should procure the services of a home tutor for their children with dyslexia among others. Keywords: Home Tutoring Programme,Reading Achievement ,Primary School and Children with Dyslexic Learning Disabilities